A stroke of genius: Predicting the next move in badminton - Ibh, M.; Graßhof, S.; Hansen, D. W. (Proceedings of the IEEE/CVF Conference on Computer Vision and Pattern Recognition (CVPR) Workshops, 2024)
This paper presents a transformer encoder-decoder model for predicting future badminton strokes based on previous rally actions. The model uses court position skeleton poses and player-specific embeddings to learn stroke and player-specific latent representations in a spatiotemporal encoder module. The representations are then used to condition the subsequent strokes in a decoder module through rally-aware fusion blocks which provide additional relevant strategic and technical considerations to make more informed predictions. RallyTemPose shows improved forecasting accuracy compared to traditional sequential methods on two real-world badminton datasets. The performance boost can also be attributed to the inclusion of improved stroke embeddings extracted from the latent representation of a pre-trained large-language model subjected to detailed text descriptions of stroke descriptions. In the discussion the latent representations learned by the encoder module show useful properties regarding player analysis and comparisons.